Grammatical Errors on EFL Students’ Conversation Practice: Surface Strategy Taxonomy - Resti Citra Dewi, Fitria Hardini Rangkuti, Supriadi (Journal of Education and Teaching Learning, 2021)
The purpose of this study was to analyze grammatical errors on EFL students’ conversation practice. The participants of this study were the fourth term students of Indonesia Institute of Technology and Business, 2020/2021 academic year. The participants taken as the object of this study because after observation in the students’ class found that there were some mistakes on the students’ speech when doing the conversation in English. The population of this study was from English Training class consisted of four parallel classes Semester IV with the total number of the students was 95 students. Purposive sampling technique was used in this study. This study was conducted by using descriptive qualitative research. The data was words, phrases, and sentences which uttered by the students and writing all non-verbal linguistic that students do on their conversation practice. The data was analyzed based on a classification of errors proposed by Dulay, Burt, and Krashen (1982 in Ellis and Barkhuizen, 2005) called Surface Strategy Taxonomy is applied. The errors in students’ speech were classified by using surface structure taxonomy namely misformation, misorder, addition, and omission. The findings of this study show that omission is the most dominant error produced by participants with the percentage 41.30%. It is followed by misformation with total cases 28.26%, addition with total cases 21.73%, and the last followed by misordering with total cases 8.69%.